Assessment of groundwater vulnerability using GOD index and Dar Zarrouk parameters: A case study of OAUSTECH main campus, Okitipupa, Ondo State - Adegoke Ige Aladeboyeje; Tolulope Temitope Adenoye; Okechukwu Ebuka Agbasi (Results in Earth Sciences)
Groundwater is essential for efficient management of groundwater to prevent the deterioration of its quality. The objective of this study is to evaluate the vulnerability of the primary campus of (Olusegun Agagu University of Science and Technology) OAUSTECH in Okitipupa, Ondo State, Nigeria. This was done by analysing the GOD index and the Dar Zarrouk parameters of conductance and transverse resistance. A total of 24 Vertical Electrical Sounding (VES) data points were gathered, with AB/2 values varying from 200 to 225. These data points were then analysed utilising partial curve matching and computer iteration techniques to determine geoelectric characteristics, including resistivity and thickness. The computed characteristics, longitudinal conductance and transverse resistance, suggest that the aquifer's ability to defend against contamination in the research area is generally insufficient. The longitudinal conductance values range from 0.02 to 0.6, with most values below 0.1. Using the GOD method, the study shows that the GOD index value varies from 0.2 to 0.6, with an average of 0.325, suggesting a moderate to high level of vulnerability in the groundwater. The association between the GOD index and longitudinal conductance results in a 60 % accuracy in predicting groundwater susceptibility. This research emphasises that the groundwater within the main campus of OAUSTECH is moderately to highly vulnerable.